KOMPETENSI PEDAGOGIS GURU DALAM PENGEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI PADA GUGUS SEKOLAH 11 ARJOWINANGUN KOTA MALANG - rina rinawijayanti; muhammad akbar (Universitas Muhammadiyah Surabaya, 2016)
This study was conducted to determine (1) the business conducted by the teacher to provide the infrastructure basis for development of social‐emotional early childhood (2) the learning process for the development of social‐emotional already implemented teacher at school (3) the monitoring and evaluation of development capabilities social‐emotional early childhood teachers in the school have been implemented. This study uses a qualitative case study method, and Spradley models using analytical techniques. Based on the research conducted, the research aspects of the provision of infrastructure facilities basic social development emotional early childhood are: (1) teachers do not have a description of the tools for social development emotional early childhood, (2) development of social skills emotional early childhood was centered on the teacher, (3) emotional social learning tools that have not been revitalized. In the aspect of the process and strategy for the establishment of social and emotional learning, is only focused on imitation and habituation and there has been no specific program of habituation behavior with the specific objective of social aspects of emotional development of young children. While the monitoring and evaluation aspects: (1) monitoring and evaluation efforts are not focused on the child, but the ending or the result of imitation that has been done, (2) monitoring and evaluation of social emotional learning only at the end or summarize the behavior of pupils. (3) psikotes AUD never become reference material preparation of the learning program. (4) monitoring and evaluation of social emotional learning only take place if there are obstacles or disputes pupil.